Contemporary Peacemaking
XXVII, 623 p. 6 illus., 3 illus. in color.
Keywords: “This is without doubt a ‘go to’ book for students, scholars, diplomats, and NGO practitioners as well as those people whose lives have been torn apart by conflict and who are working to change the opportunities for their communities.” —Jonathan Cohen, Executive Director, Conciliation Resources “Contemporary Peacemaking offers an overview that is comprehensive in both sweep and detail. It shows how understanding that power lies at the heart of the peacemaking enterprise, just as it is in the core of conflict, can open the way for a peaceful settlement.” —Dan Smith, Director, Stockholm International Peace Research Institute (SIPRI) “This multi-perspective book gives us the state of the art tools we need to understand the problems and the possibilities of effective peacemaking. Bringing new voices and issues into the discussion of peacemaking, this volume makes a vital contribution in explaining the state of the contemporary field.It will be of great value to those new to peacemaking and those who have long-term interests in it.” —Joanna Spear, Director, FAO Regional Skill Sustainment Initiative & Associate Professor, The George Washington University, USA This fully updated third edition of Contemporary Peacemaking is a state of the art overview of peacemaking in relation to contemporary civil wars. It examines best (and worst) practice in relation to peace processes and peace accords. The contributing authors are a mix of leading academics and practitioners with expert knowledge of a wide array of cases and techniques. The book provides a mix of theory and concept-building along with insights into ongoing cases of peace processes and post-accord peacebuilding. The chapters make clear that peacemaking is a dynamic field, with new practices in peacemaking techniques, changes to the international peace support architecture, and greater awareness of key issues such as gender and development after peace accords. The book is mindful of the intersection between top-down and bottom-up approaches to peace and how formal and institutionalized peace accords need to be lived and enacted by communities on the ground. Roger Mac Ginty is Professor at the School of Government and International Affairs, and Director of the Durham Global Security Institute, both at Durham University, UK. Anthony Wanis-St. John is Associate Professor at the School of International Service at American University, USA, where he directed the International Peace and Conflict Resolution program.